Gaze-contingent training enhances perceptual skill acquisition - Ryu, D.; Mann, D. L.; Abernethy, B.; Poolton, J. M. (Journal of Vision, 2016)
The purpose of this study was to determine whether decision-making skill in perceptual-cognitive tasks could be enhanced using a training technique that impaired selective areas of the visual field. Recreational basketball players performed perceptual training over 3 days while viewing with a gaze-contingent manipulation that displayed either (a) a moving window (clear central and blurred peripheral vision), (b) a moving mask (blurred central and clear peripheral vision), or (c) full (unrestricted) vision. During the training, participants watched video clips of basketball play and at the conclusion of each clip made a decision about to which teammate the player in possession of the ball should pass. A further control group watched unrelated videos with full vision. The effects of training were assessed using separate tests of decision-making skill conducted in a pretest, posttest, and 2-week retention test. The accuracy of decision making was greater in the posttest than in the pretest for all three intervention groups when compared with the control group. Remarkably, training with blurred peripheral vision resulted in a further improvement in performance from posttest to retention test that was not apparent for the other groups. The type of training had no measurable impact on the visual search strategies of the participants, and so the training improvements appear to be grounded in changes in information pickup. The findings show that learning with impaired peripheral vision offers a promising form of training to support improvements in perceptual skill.